Comparison of intravenous iron sucrose with oral iron in pregnant women with iron deficiency anaemia - Rudra, Samar; Chandna, Archana; Nath, Jayati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The aim of this study was to compare the efficacy and safety of intravenous iron sucrose with oral iron in the treatment of iron deficiency anaemia in pregnancy. Methods: 200 pregnant women with gestational age between 24 to 34 weeks with Hb 7.0-9.0 g/dL and peripheral smear features suggestive of iron deficiency anaemia were included in the study and they were randomized in two groups of 100 each. Group A: IV iron group was given 200 mg of Iron sucrose complex in 200 ml of normal saline IV drip, 3 days a week till her calculated required dose has been infused. Group B: oral iron group received ferrous ascorbate oral tablets equivalent to 100 mg elemental iron twice a day during her pregnancy. Various laboratory parameters like hemoglobin, reticulocyte count, PCV, MCV, MCH, MCHC as well as serum ferritin were measured at recruitment and at 1week, 2 weeks, 4 weeks of starting treatment, at delivery and at 3 months postpartum. Haemoglobin and ferritin level of cord blood was also measured. Any adverse effects of drug were noted in both the groups. All the relevant data were tabulated and statistical analysis was done. Results: The change in all the assessed parameters including haemoglobin and ferritin levels from baseline was significantly higher in the intravenous group than the oral group at each point of measurement. IV iron group did not have any serious adverse drug reactions and oral group experienced adverse effects mainly gastrointestinal symptoms. Conclusions: Intravenous iron sucrose treated iron deficiency anaemia of pregnancy faster, and more effectively than oral iron therapy, with no serious adverse drug reactions.